An altered pattern of myocardial histopathological and molecular changes underlies the different characteristics of type-1 and type-2 diabetic cardiac dysfunction - Radovits, Tamás; Korkmaz-İçöz, Sevil; Mátyás, Csaba; Oláh, Attila; Németh, Balázs Tamás; Páli, Szabolcs; Hirschberg, Kristóf; Zubarevich, Alina; Gwanmesia, Patricia Neh; Li, Shiliang; Loganathan, Sivakkanan; Barnucz, Enikő; et al. (Journal of diabetes research, 2015)
Increasing evidence suggests that both types of diabetes mellitus (DM) lead to cardiac structural and functional changes. In this study we investigated and compared functional characteristics and underlying subcellular pathological features in rat models of type-1 and type-2 diabetic cardiomyopathy. Type-1 DM was induced by streptozotocin. For type-2 DM, Zucker Diabetic Fatty (ZDF) rats were used. Left ventricular pressure-volume analysis was performed to assess cardiac function. Myocardial nitrotyrosine immunohistochemistry, TUNEL assay, hematoxylin-eosin, and Masson’s trichrome staining were performed. mRNA and protein expression were quantified by qRT-PCR and Western blot. Marked systolic dysfunction in type-1 DM was associated with severe nitrooxidative stress, apoptosis, and fibrosis. These pathological features were less pronounced or absent, while cardiomyocyte hypertrophy was comparable in type-2 DM, which was associated with unaltered systolic function and increased diastolic stiffness. mRNA-expression of hypertrophy markers c-fos, c-jun, and β-MHC, as well as pro-apoptotic caspase-12, was elevated in type-1, while it remained unaltered or only slightly increased in type-2 DM. Expression of the profibrotic TGF-β1 was upregulated in type-1 and showed a decrease in type-2 DM. We compared type-1 and type-2 diabetic cardiomyopathy in standard rat models and described an altered pattern of key pathophysiological features in the diabetic heart and corresponding functional consequences.